Annexin A5 is involved in migration and invasion of oral carcinoma - Wehder, Liane; Arndt, Stephanie; Murzik, Ulrike; Kob, Robert; Von Eggeling, Ferdinand; Melle, Christian; Bosserhoff, Anja Katrin (Cell Cycle, 2009)
Annexin A5 is a Ca(2+)-binding protein which is involved in membrane organization and dynamics. As recent data suggest a role of annexin A5 in cancer we aimed to gain more insight into the biological function of endogenous annexin A5 and assessed its possible influence on proliferation and invasion capacity. We downregulated annexin A5 by RNA interference in HaCaT keratinocytes, squamous carcinoma cell line A431 as well as in a primary cell culture of a human oral carcinoma. Hereby, we detected reduced migration and invasion capacity of HaCaT cells which was even stronger in the oral carcinoma. To determine target genes of annexin A5 we used a metastasis specific microarray. Thereby, genes implicated in cell motility including S100A4, TIMP-3 and RHOC were observed to be regulated. These deregulations were confirmed by RT-PCR or western blots, respectively. These observations suggest that the invasion capacity, a main characteristic of tumors, is at least partially regulated by annexin A5 in oral carcinoma.
Keywords: annexin A5; migration; invasion; proliferation; metastasis; oral carcinoma